METHOD VALIDATION OF SIMVASTATIN IN PCL-PEG-PCL TRIBLOCK COPOLYMER MICELLES USING UV-VIS SPECTROPHOTOMETRIC FOR SOLUBILITY ENHANCEMENT ASSAY - PATMAYUNI, DEWI; SULAIMAN, T. N. SAIFULLAH; ZULKARNAIN, ABDUL KARIM; SHIYAN, SHAUM (International Journal of Applied Pharmaceutics, 2022)
Objective: This study aims to increase the solubility of simvastatin (SIM), a hydrophobic drug, by incorporating it into PCL-PEG-PCL triblock copolymer micelles and validating the assay method used, namely Uv-Vis spectrophotometric. Methods: The shake flask method was used to determine the increase in solubility experienced by SIM after being incorporated into the micellar system. The values ​​of maximum wavelength (λmax), linearity, LOD, LOQ, accuracy, and precision were used as parameters measured to assess the validity of the assay method used. Results: The results showed that PCL-PEG-PCL triblock copolymer micelles could increase SIM solubility by 9.7 times (89.49±5.75 µg/ml) compared to SIM without modification (9.19±0.24 µg/ml). The validation results show the λmax value of 239 nm, a linear calibration curve with an R-value of 0.9994, LOD and LOQ of 0.33 µg/ml and 1.00 µg/ml, accurate measurement with recovery at concentrations of 80%, 100%, and 120% were 102.93±1.32%, 100.78±0.40%, and 104.58±0.79% and also had good precision ​​with RSD<2%. Conclusion: The PCL-PEG-PCL triblock copolymer micelles can increase SIM solubility and the Uv-Vis spectrophotometric method has been validated successfully for the quantitative analysis of SIM in PCL-PEG-PCL triblock copolymer micelles.